Effects of Bonny-light Crude oil Contaminated-diet on Some Antioxidant Enzymes and Body Weight Changes of Wistar Albino Rats (African Journal of Biomedical Research, 2023)
Albino rats were fed on commercial rat feeds contaminated with Bonny-light crude oil of varying concentrations of 1%, 5% and 10% for 28 days. Feed and water were provided ad libitum throughout the experimental period. The mean body weights of the rats were taken one week into the treatment and at the end of the treatment. A gradual decrease in body weight was recorded with respect to control. A decrease in feed consumption rate with increasing concentration of the toxicant with respect to the control was recorded. Blood was drawn from ocular cantus vein and analyzed. A high increase in lipid oxidation, which was higher in males than in females, was recorded. There was a significant increase glutathione s- transferase activity in the 1% and 5% groups and a significant decrease in 10% group (P≤0.05). A significant increase in superoxide dismutase activity was recorded in all the groups with respect to the parallel control group.